The coexistence of oral lichen planus and psoriasis vulgaris - a case report - Paulina Kiluk; Iwona Flisiak (Termedia Publishing House, 2016)
Introduction . Psoriasis and lichen planus are common dermatological conditions, whose coexistence is rarely described. Although the exact etiopathogenesis of both diseases is still unknown, autoimmune factors play an important role in their development. A common feature is also the occurrence of the Köbner phenomenon. The principal differences concern the clinical, histological and immunological events. Objective. To present a patient with oral lichen planus, in whom psoriasis developed. Case report. A 75-year-old patient, with a 3-year history of oral lichen planus, presented itchy erythematous skin lesions initially located in the intertriginous area. Outpatient treatment consisting of topical and oral antifungal medications did not bring significant improvement. Skin biopsy confirmed the diagnosis of psoriasis. Treatment with tar ointment and topical tacrolimus was carried out, resulting in gradual improvement. Conclusions . A review of the literature indicates the existence of possible, but still unexplained, linkages between these two diseases.